2015
DOI: 10.1038/ismej.2015.57
|View full text |Cite
|
Sign up to set email alerts
|

Forest harvesting reduces the soil metagenomic potential for biomass decomposition

Abstract: Soil is the key resource that must be managed to ensure sustainable forest productivity. Soil microbial communities mediate numerous essential ecosystem functions, and recent studies show that forest harvesting alters soil community composition. From a long-term soil productivity study site in a temperate coniferous forest in British Columbia, 21 forest soil shotgun metagenomes were generated, totaling 187 Gb. A method to analyze unassembled metagenome reads from the complex community was optimized and validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 53 publications
3
62
0
2
Order By: Relevance
“…Combining our results with their finding, we suggested that CWD could be considered to be spots where both pedogenic and microbial processes are concentrated. It could confirm the importance of appropriate CWD management in the context of sustaining soil functioning and fertility [9][10][11][12].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Combining our results with their finding, we suggested that CWD could be considered to be spots where both pedogenic and microbial processes are concentrated. It could confirm the importance of appropriate CWD management in the context of sustaining soil functioning and fertility [9][10][11][12].…”
Section: Discussionmentioning
confidence: 83%
“…Recent studies have found negative effects of CWD removal on soil nitrogen (N) availability and C pool as well as soil microbial communities and metabolic potential [10][11][12]. However, the interaction between CWD and soils remains one of the most unknown subjects in forest ecology.…”
Section: Introductionmentioning
confidence: 99%
“…Total OC (%) plays a strong role in shaping the relative abundance of GH families in situ, as shown by greater richness of GH families involved in cellulose, hemicellulose, lignin and pectin degradation in relatively C rich organic soil layers compared to a greater relative abundance of phenol and protein degradation in C poor mineral soil layers (Cardenas et al, 2015;de Menezes et al, 2015;Uroz et al, 2013). Comparative analysis of a relatively C rich grassland soil showed preferential enrichment of GH families involved in cellobiose and amine degradation while a relatively C poor wheat cropping soil enriched for GH families involved in chitin, b-N-acetylglucosamine and glycoside degradation (Manoharan et al, 2015).…”
Section: Extracellular Enzyme Activitymentioning
confidence: 99%
“…Forest soil profiles typically consist of a root-entangled mat of partially decomposed plant litter (organic horizon) that sits atop a less-carbon-rich mineral soil. The functional (13) and taxonomic (14) compositions of microbial communities are similarly stratified, with the organic horizon more enriched in fungi and carbohydrate-degrading genes than the mineral soil (15). Forest organic horizon communities have previously been shown to respond to environmental stressors with greater functional (15) and taxonomic (16) shifts than those of the mineral soil, indicating that evaluating the horizon-specific responses to warming may provide insight into altered microbial carbon cycling capacity.…”
Section: Introductionmentioning
confidence: 99%